2014
DOI: 10.1007/s10067-014-2771-3
|View full text |Cite
|
Sign up to set email alerts
|

PECAM-1 gene polymorphisms and soluble PECAM-1 level in rheumatoid arthritis and systemic lupus erythematosus patients: any link with clinical atherosclerotic events?

Abstract: Genetic polymorphisms of platelet endothelial cell adhesion molecule-1 (PECAM-1) were found to play roles in atherosclerotic events. We determined PECAM-1 polymorphisms, soluble PECAM-1, and CD40L levels in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) and evaluated their associations with clinical atherosclerotic complications. We included 100 RA patients, 81 SLE patients, and 94 healthy controls. The clinical features about the patients were obtained from medical records. Past cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…Nevertheless, another adhesion molecule, PECAM-1, was significantly upregulated in the NK cells of RA patients. This finding is in line with a similar study reporting high levels of serum-soluble PECAM-1 in RA patients [42]. In NK cells, PECAM-1 was found to play a crucial role in NK cell extravasation into tissues and inflammatory sites [43].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, another adhesion molecule, PECAM-1, was significantly upregulated in the NK cells of RA patients. This finding is in line with a similar study reporting high levels of serum-soluble PECAM-1 in RA patients [42]. In NK cells, PECAM-1 was found to play a crucial role in NK cell extravasation into tissues and inflammatory sites [43].…”
Section: Discussionsupporting
confidence: 91%
“…In another study, however, sPECAM level was found to be not different from the control group [ 61 ]. Discrepancies in the studies make it difficult to reach a final conclusion, and the role of PECAM-1 as a biomarker of endothelial injury in lupus is not established yet.…”
Section: Immunoglobulin Supergene Family Moleculesmentioning
confidence: 90%
“…A few studies that have investigated the relationship between PECAM-1 levels in patients with SLE found PECAM-1 elevated [ 27 ], but this has not been confirmed by the results of all the studies [ 61 ].…”
Section: Immunoglobulin Supergene Family Moleculesmentioning
confidence: 99%
“…Platelet endothelial cell adhesion molecule (PECAM-1, also known as CD31) is highly expressed in blood platelets. Studies have revealed that PECAM-1 is involved in heart development, and in adults, PECAM-1 influences the prognosis of cardiovascular disease via inflammatory response and the regulation of endothelium integrity [14]. Increased expression of PECAM-1 has been associated with poor prognosis of myocardial infarction [15].…”
Section: Salvia Miltiorrhiza Injection (Also Known Asmentioning
confidence: 99%